The Influence of Financial Performance, Company Characteristics, Corporate Governance and Audit Opinion on Audit Delay (In Basic Chemical Companies in Indonesia) - Agus Rahman Alamsyah (Politeknik Siber Cerdika Internasional, 2026)
Background: Timely submission of audited financial reports is fundamental to market transparency and stakeholder confidence. Delays in the audit process diminish the relevance of financial information, potentially distorting investor decision-making and undermining capital market efficiency. Despite regulatory frameworks establishing strict deadlines, audit delays remain a persistent issue among Indonesian publicly listed companies. In the basic chemical subsector—strategically important for supporting broader manufacturing activity—understanding the drivers of audit delay has both practical and academic significance. Objective: This study aims to analyze the influence of financial performance (ROA), company characteristics (firm size), corporate governance (audit committee), and audit opinion on audit delays in basic chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016–2023. Methods: Using purposive sampling, 13 of 17 eligible companies were selected, yielding 104 company-year observations. Logistic regression was employed as the primary analytical technique, given the dichotomous nature of the audit delay dependent variable. Results: Financial performance (ROA) and company size do not significantly affect audit delays. Corporate governance, as proxied by audit committee size, has a significant negative effect on audit delays (p = 0.009). The audit opinion variable could not be statistically tested due to the absence of variation—all sampled companies consistently received unqualified opinions throughout the observation period. Conclusion: Corporate governance—specifically the presence of an effective audit committee—is the most critical determinant of audit efficiency in this sector. The homogeneity of audit opinions reflects the subsector's high compliance with financial reporting standards, though it limits the empirical scope of this study. Future research should broaden the sample to allow for greater variation in audit opinion types and incorporate additional governance variables.